The Exercise Model of Shooting Skills for the Beginner Players Women's of Futsal - Ahmad Rizal; Hernawan Hernawan; Iman Sulaiman (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The aim of this study is to develop a shooting skill exercise model design for beginner players women's of futsal to obtain empirical data about the effectiveness of the results of shooting skill exercise models for beginner players women's of futsal. The method used in this study is the research and development method of Borg and Gall which consists of ten steps. The subject of this research is a beginner woman futsal player. The final results of this study are model manuals and shooting skills exercise video models for woman futsal players with a final model number of 27 models that have gone through expert evaluation, trial and revision, and effectiveness has been tested. The effectiveness of the application of shooting skills exercise models for woman futsal beginners uses the "t-test" technique. p data on the results of the pretest and posttest shooting skill training for beginner woman futsal players with a significance level of 0.05. The results of shooting skills training for woman futsal beginner players between pretest is 2.0645 with posttest of 2.9294 (at a significance level of 0.05), then it shows that the results of the increase in the post-test group are higher than the pre-test group. Thus it can be stated that, the shooting skill exercise model for beginner woman futsal players is effectively used to improve the results of shooting skills beginner woman futsal players. Thus it can be stated that, the shooting skill training model for beginner woman futsal players is effectively used to improve the results of shooting skills.